QTL Analysis of Genetic Main Effects and Genotype (Environment Interaction Effects for Yield Components in Rice Oryza sativa L.) - Mebrouk Benmoussa; ZHU Jun; YAN Ju-qiang; HE Ci-xin; WU Ping (浙江大学学报. 农业与生命科学版)
Quantitative trait loci (QTL) for yield components were identified based on an RFLP map from a DH population. The 123 double haploid lines with their parents IR64 and Azucena were evaluated in the field in two different environments (Hangzhou and Hainan). Genetic main effects and GE interaction effects were predicted by an adjusted unbiased prediction (AUP) method and used in QTL mapping. The results indicated that some QTLs detected with QTL main effects might also have QTL environment (QE) interaction effects. In contrast some identified QTLs were mainly controlled by QE interaction effects without significant QTL main effects. The study also indicated that individual QTL showed a range of sensibility to environments as some QTLs were detected only in a single environment while others were detected in two environments. It is also shown that QTL associated with yield components (total grains and full grains) had large additive effects for both QTL main effects and QE interaction effects. These QTLs seem to act as major gene in both environments.